Deconstructing the Japanese genkan for the next normal - Gallardo, Rujena Mei A. (College of Home Economics, University of the Philippines Diliman, 2021)
This qualitative case study aimed to study the adaptability of the Japanese genkan for Filipino home entrances. The motivations and characteristics of this space were discussed to understand how the genkan is used in Japanese households, and how it could be translated for use in Filipino homes. Japan's history, design philosophies, and views on health were compared with that of the Philippines' to further understand how the genkan can be adapted. With this, the theory of cultural relativism was used. Research on Japan and the Philippines and interviews with relevant informants were conducted online. The study found that the genkan is able to promote its intended use through its inherent design, thus encapsulating the design philosophies of Japan. It is able to communicate its use visually, without disrupting the flow of the user. In its history, the use of the genkan has changed with their political climate, during Japan's era of cultural enrichment. The concept of spatial and spiritual inside and outside is similar with the Philippine concept of labas and loob as well, indicating how each culture sees health in a way that respects others. While the cultures are similar, a properly furnished foyer or entrance is still able to do the same job as the genkan. However, Philippine philosophies such as horror vacui and tropical design are easily adaptable and add to how the genkan can add to its supportability for Filipinos. It is recommended to gauge interest in the genkan among Filipino homeowners, as well as doing further research into how universal design applies to the space. More respondents is also recommended to gain more perspectives on the subject.